Association of five genetic variations in DNMT1 and DNMT3A with gastric cancer in a Chinese population. (29th June 2018) - Zhou, Jin; Wang, Zhibing; Zhang, Lei; Gu, Yuanyuan; Ma, Yong; Li, Xiangcheng
Aim: To determine whether genetic variations in DNMT1 and DNMT3A could be associated with gastric cancer risk.Materials & methods: A total of 466 patients and 452 healthy controls were enrolled in this study. Genotypes were examined by using the Sequenom MassARRAY platform.Results: No significant differences in the distribution frequencies were observed between the groups. However, subgroup analysis revealed that, in the group aged ≤60 years, DNMT3A rs13420827 was associated with reduced gastric cancer risk, and that carrier of GC/GG genotype was associated with reduced risk of gastric cancer with low differentiation or at the T3–T4 stage.Conclusion: This study suggests that five genetic variations of interest in DNMT1 and DNMT3A are not associated with the presence of gastric cancer, but that rs13420827 may contribute to the gastric cancer risk for those younger individuals, the risk of which may be influenced by the characteristics of tumor.